Real options and option-embedded securities /,Real options & option-embedded securities - Moore, William T.
Real options and option-embedded securities / / William T. Moore. .- New York : : John Wiley, , c2001. .- vi, 294 p. : : ill. ; ; 24 cm. .- 0471216593